Konsep modal insan rabbani menurut al-Quran: Analisis pemikiran sa‘id hawwa dalam al-Asas fi al-Tafsir / Muhamad Alihanafiah Norasid - Muhamad Alihanafiah , Norasid (2016)

(untitled)
This study discusses the concept of rabbani human capital according to the Qur'an and analyses the rabbani human capital idea of Sa‘id Hawwa in the work of al-Asas fi al-Tafsir. The concept of human capital from Qur’anic perspective is expounded by examining the human capital component which consists of body and soul, while the spiritual features comprise of fitrah, ‘aql, qalb, ruh and nafs. Additionally the definition of “rabbani” from Quranic perspective is analysed thematically. The combination of the concept of human capital with the term “rabbani” shows that the concept of “rabbani” is the value indicator in actualising human capital development in a holistic manner. This study selected Sa‘id Hawwa as its subject because he was a murabbi figure who critically conveyed ideas of rabbani human capital development in his works. This qualitative study applied the documentation method, historical method, interview method, and exploration method as methods of data collection, whereas the inductive method, deductive method, comparative method, and text analysis method were adopted for data analysis. The analysis found that there are three core components of development that should be developed to produce rabbani human capital, which are the application of rabbani knowledge, strengthening rabbani tarbiyah, and the development of rabbani dakwa. The three components of rabbani human capital as envisioned by Sa‘id Hawwa were structured on the texts of the Qur’an that contain the word “rabbani”. The idea of rabbani human capital development is seen as capable of developing a holistic and balanced human capital. Sa‘id Hawwa also placed the mosque institution as the main medium for the development of rabbani human capital by expanding its function as an education hub, with integrated Islamic curriculum, centre of spiritual tarbiyah and institution for dakwa training.